Investigation of time diversity as rain fade mitigation technique for ka-band satellite-earth link in tropical region - Nur Liyana Izyan binti Jamaludin (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
The frequency spectrum congestion experienced by satellite broadcasting links has initiated the idea of migration from lower frequency bands of broadcasting signals to higher frequency bands. As higher frequency band is used, the wavelength is reduced even to millimetre scale and caused the signal to attenuate higher especially during the rainy conditions. The tropical regions typically experience severe rainfall rate; of about 145 mm/hr at exceedance of 0.01% of year average time. The severity of the rain affects the quality of signals being transmitted during this period. This problem even poses financial risks especially for commercial broadcasting applications such as video-on-demand. There are various mitigation techniques that are currently being studied. This research focused on time-diversity mitigation technique which involves a process of retransmission of signals to obtain the better signal for best output. The study formulates a mathematical model which might enables the usage of Ka-band frequency in Tropical regions. Preliminary analyses include the time series generation for the rain events and creation of annual cumulative distributions. The time diversity of fifteen minutes had generated in more than II dB improvement from the original signal attenuation at 0.01% of signal outage which equivalent to 99.99% of link availability of the average year. Mathematical model for time diversity gain as a function of delay was obtained in terms of regression coefficients of alpha and beta as a function oftime delays; which then portrayed in time diversity delays as a function of time delay curve.